2001
DOI: 10.1097/00001648-200111000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Update of the Follow-Up of Mortality and Cancer Incidence among European Workers Employed in the Vinyl Chloride Industry

Abstract: Although vinyl chloride is an established cause of liver angiosarcoma, the evidence is inconclusive on whether it also causes other neoplastic and nonneoplastic chronic liver diseases as well as neoplasms in other organs. Furthermore, the shape of the dose-response relation for angiosarcoma is uncertain. We have extended for approximately 8 years the mortality and cancer incidence follow-up of 12,700 male workers in the vinyl chloride industry in four European countries. All-cause mortality was lower than expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 31 publications
5
99
0
Order By: Relevance
“…Various European and Italian studies have reported the apparent association between the amount and timing of exposure to VCM and development of HCC in those exposed [118][119][120] .…”
Section: Vcm and Polyvinyl Chloridementioning
confidence: 99%
“…Various European and Italian studies have reported the apparent association between the amount and timing of exposure to VCM and development of HCC in those exposed [118][119][120] .…”
Section: Vcm and Polyvinyl Chloridementioning
confidence: 99%
“…Their results are also available as detailed reports (6)(7). These studies combine populations of exposed workers included in previous investigations and extend the follow-up.…”
mentioning
confidence: 99%
“…Two large, multicenter epidemiologic studies of workers exposed to vinyl chloride have been reported recently (4)(5). Their results are also available as detailed reports (6)(7).…”
mentioning
confidence: 99%
“…However, the actual incidence of angiosarcoma of the liver and hepatocellular carcinoma for workers employed after 1975 is lower than those employed before this time, with an increased latency period for the development of cancer in those employed after 1975 [45,53]. The link between liver cancer and VCM is now well established, with these results being witnessed in other studies, and further confirmed by the follow-up studies of these original cohorts [53][54][55][56].…”
Section: History Of Recognition Of Issues With Vcm and Setting Of Expmentioning
confidence: 91%